2020
DOI: 10.21203/rs.3.rs-26196/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxychloroquine-Induced Stevens-Johnson Syndrome in COVID-19: A rare Case Report

Abstract: Background: The international outbreak of respiratory illness termed coronavirus disease 2019 (COVID-19) began in December 2019 that has affected more than 0.8 million individuals. To date, there are no specific therapeutic agents for coronavirus infections. One of the drugs that have an effective role in improving the condition of patients with COVID-19 is hydroxychloroquine (HCQ). This drug is not a definitive treatment for this disease and has a supportive role. Like all medications, HCQ has side effects an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…We have evaluated 20 case reports including 25 cases of COVID‐19 who were treated with multiple drugs in Table 1 4‐23 . In Tables 2, 4 cohort studies are shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have evaluated 20 case reports including 25 cases of COVID‐19 who were treated with multiple drugs in Table 1 4‐23 . In Tables 2, 4 cohort studies are shown.…”
Section: Resultsmentioning
confidence: 99%
“…It should be notified that logically the rate of dermatologic adverse effects among antivirals is related to their frequency of usage, too. Since, adverse drug reactions of skin are frequently observed in pandemic area, dermatologist and specialists of other fields really need to be more informed about drugs with more mucocutaneous adverse reactions and the type of reactions and some of these reactions may be severe or even life‐threatening also management of patients in such conditions could be really challenging regarding skin eruption and concomitant COVID infection 4,19,20 . The authors of this study have been focused on various aspects of COVID‐19 especially in the field of dermatology and now it seems that focus on this topic is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HCQ-induced drug reactions became one of the challenges in dermatology practice. Acute generalized exanthematic pustulosis, 60 , 61 , 62 Stevens-Johnson syndrome, 63 maculopapular and urticarial rashes, 64 drug reaction with eosinophilia and systemic symptoms syndrome, 65 and itching 64 are known cutaneous reactions of HCQ. Another potential hazard is the exacerbation of psoriasis.…”
Section: New Challengesmentioning
confidence: 99%
“… 66 Iranian dermatologists managed many patients with such reactions in e-visits, e-consults, in-person visits, dermatology wards, and COVID-19 services. 63 There are recent reports regarding HCQ cardiotoxicity and questionable efficacy. 67 , 68 …”
Section: New Challengesmentioning
confidence: 99%
“…), gastrointestinal adverse reactions, hepatic adverse reactions (hepatitis and increased liver enzymes), etc. Results of a recent case report emphasized that chloroquine/hydroxychloroquine administration could induce severe dermatologic side effects such as Stevens Johnson syndrome (SJS) in a patient with COVID-1950 . Also the results of a systematic review on dermatologic adverse effects of hydroxychloroquine emphasized that the most common dermatologic reactions due to hydroxychloroquine administration were rash, SJS, toxic epidermal necrolysis (TEN),…”
mentioning
confidence: 99%